The law of possession: ritual, healing, and the secular state - Sax, William Sturman; Basu, Helene (Oxford University Press, 2015)
Rituals combining healing with spirit possession and court-like proceedings are found around the world and throughout history. Modern, secular states have systematically attempted to eliminate them. 'The Law of Possession' compares and analyses the internal logic of such practices, as well as their relation to the modern, secular state.